Potensi Senyawa Volatil dari Khamir untuk Mengendalikan Cercospora coffeicola : Potency of Yeast’s Volatile Compounds to Control Cercospora coffeicola - Hartati, Sri; Meliansyah, Rika; Mayanti, Tri (Jurnal Fitopatologi Indonesia, 2024)
Potency of Yeast’s Volatile Compounds to Control Cercospora coffeicolaCercospora leaf spot caused by Cercospora coffeicola is a major disease on coffee plants. Antifungal volatiles produced by some antagonistic agents can be useful in biological control approach of this pathogen. Some yeasts have been reported to produce antifungal volatiles and may have the potency as antagonistic agents against fungal pathogens. This research was aimed to determine the morphological characteristics of the yeast isolates and their ability to suppress C. coffeicola by producing antifungal volatiles. The yeasts were isolated from coffee leaves and berries grown in several location at Kecamatan Cilengkrang, Kabupaten Bandung and Kecamatan Jatinangor, Kabupaten Sumedang. The research was started by isolation of yeasts and followed by morphological characterization of yeasts’ colony. The potency of the volatiles produced by the antagonistic isolates were tested in vitro using double dish system. As many as 52 yeast isolates were obtained. The dominant colors of the yeasts colonies on PDA were white, cream, and orange, with smooth, serrated, and filamentous edges. The colony shapes were round to irregular. The microscopic observation showed that the cells were round, ovate, and elongated, with the size ranged around 2.59-18.13 × 1.23-7.77 µm. Those yeasts isolates were able to suppress the growth of C. coffeicola by the activity of antifungal volatile compound, with the inhibition level of 11.85% to 79.26%. The results showed that all the isolates were capable to inhibit the in vitro growth of C. coffeicola.